On Topological Analysis of Entropy Measures for Silicon Carbides Networks - Xing-Long Wang; Muhammad Kamran Siddiqui; Syed Ajaz K. Kirmani; Shazia Manzoor; Sarfraz Ahmad; Mlamuli Dhlamini (Complexity)
The silicon material has provoked and stimulated significant research concern to a considerable extent taking into account its marvelous mechanical, optical, and electronic properties. Naturally, silicons are semiconductors and are utilized in the formation of various materials. For example, it is used in assembling the electronic based gadgets. In this article, we have studied the 2D structure of silicon carbide Si2C3−Im,n and Si2C3−IIm,n and then continued to discuss some degree grounded topological descriptors in association with their corresponding entropy measures. We extend this computation to the quantitative and pictorial comparisons which could be beneficial in the structure amendment for effective implementation.